(untitled) (Confluenţe Bibliologice, 2025)
Maia Balan, Head of the Public Library of Old Biliceni, realized an interview with Ana Sofroni, former teacher at the Department of Library Science of State University from Chişinău. From this interview we learn that she is the interpreter of the religious songs, the author of the collection of religious songs „Glimpses of Divine Light“.